Postcard from J. W. Thomas to James Curtis Booth, December 6, 1881 - Thomas, Joseph W. (1881)
Joseph W. Thomas informs James Curtis Booth (1810-1888) that it isn't too late to plant, and thanks Booth for his most recent order.
Keywords: Booth, James Curtis, 1810-1888; Nurseries (Horticulture); Thomas, Joseph W.